Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Great Amazon Reef System: A fact - Thomás N. S. Banha; Osmar J. Luiz; Nils E. Asp; Hudson T. Pinheiro; Rafael A. Magris; Ralf T. S. Cordeiro; Michel M. Mahiques; Miguel Mies; Vinicius J. Giglio; Claudia Y. Omachi; Eduardo Siegle; Luciane C. Nogueira; et al. (Frontiers in Marine Science, 2022)

Thermal plasticity of coral reef symbionts is linked to major alterations in their lipidome composition - Marina T. Botana; Adriano B. Chaves‐Filho; Alex Inague; Arthur Z. Güth; Flavia Saldanha‐Corrêa; Marius N. Müller; Paulo Y. G. Sumida; Sayuri Miyamoto; Matthias Y. Kellermann; Raymond C. Valentine; Marcos Y. Yoshinaga (Limnology and Oceanography, 2022)
Coral bleaching caused by ocean warming is leading to worldwide coral decline. The physiological processes underlying this ecological event are still incompletely understood, although previous research has suggested oxidative stress as major player in the impairment of symbiont thylakoid membranes and in symbiosis breakdown. Lipids are interesting targets of investigation, given their susceptibility to thermal and oxidative stresses. Here, an untargeted lipidomic approach was employed to examine changes in lipidome and pigments of three coral reef symbionts (Symbiodiniaceae) after a heat shock in in vitro experiments. The acute thermal stress induced species‐specific changes in lipidome and pigments compositions of both heat sensitive and tolerant symbionts. Heat sensitivity was characterized by a steep and steady decline in cell densities over time (4 and 240 h after heat shock). At the membrane level, heat sensitive symbiont displayed a quantitative decrease in glycolipids linked to polyunsaturated fatty acids, followed by enrichment in oxidized lipids and sphingolipids. Despite showing distinct adaptations, the two heat tolerant symbionts were characterized by the preservation of membrane lipids after heat shock, particularly glycolipids. This finding suggests the action of powerful antioxidant systems, preventing the escalation of oxidized lipids concentration in thylakoid membranes under thermal stress. Although limited by the examination of free‐living symbionts, our study provides a solid baseline for the investigation of lipidome and pigments alterations of Symbiodiniaceae in response to heat stress. Novel potential lipid biomarkers linked to thermal stress are suggested. In particular, oxidized lipids—which are implicated in coral symbiosis establishment and breakdown—appear as attractive targets for further research.

Low coral mortality during the most intense bleaching event ever recorded in subtropical Southwestern Atlantic reefs - T. N. S. Banha; K. C. C. Capel; M. V. Kitahara; R. B. Francini-Filho; C. L. B. Francini; P. Y. G. Sumida; M. Mies (Coral Reefs, 2020)

In situ shifts of predominance between autotrophic and heterotrophic feeding in the reef-building coral Mussismilia hispida: an approach using fatty acid trophic markers - M. Mies; A. Z. Güth; A. A. Tenório; T. N. S. Banha; L. G. Waters; P. S. Polito; S. Taniguchi; M. C. Bícego; P. Y. G. Sumida (Coral Reefs, 2018)

Cyst infection in autosomal dominant polycystic kidney disease: causative microorganisms and susceptibility to lipid-soluble antibiotics - T. Suwabe; H. Araoka; Y. Ubara; K. Kikuchi; R. Hazue; K. Mise; S. Hamanoue; T. Ueno; K. Sumida; N. Hayami; J. Hoshino; A. Imafuku; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

The effect of chronic treatment with fluoride on salivary activity, tooth, and bone in spontaneously hypertensive rats (SHR) - Daniele C. R. Picco; Alberto C. B. Delbem; Kikue T. Sassaki; Doris H. Sumida; Cristina Antoniali (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Age-dependent cognitive impairment in a Drosophila Fragile X model and its pharmacological rescue - Catherine H. Choi; Sean M. J. McBride; Brian P. Schoenfeld; David A. Liebelt; David Ferreiro; Neal J. Ferrick; Paul Hinchey; Maria Kollaros; Rebecca L. Rudominer; Allison M. Terlizzi; Eric Koenigsberg; Yan Wang; et al. (Biogerontology, 2010)

Leaf litterfall and decomposition of different above- and belowground parts of birch (Betula ermanii) trees and dwarf bamboo (Sasa kurilensis) shrubs in a young secondary forest in Northern Japan - S. K. Tripathi; A. Sumida; H. Shibata; K. Ono; S. Uemura; Y. Kodama; T. Hara (Biology and Fertility of Soils, 2006)

CYP2C19 genotypes and omeprazole metabolism after single and repeated dosing when combined with clarithromycin - Q. Zhou; I. Yamamoto; T. Fukuda; M. Ohno; A. Sumida; J. Azuma (European Journal of Clinical Pharmacology, 1999)